Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Nouvelles données paléoenvironnementales dans le Sud de la France vers 30000 ans 14C BP : le cas de la grotte Marie (Hérault) - Crochet, Jean-Yves; Gence, Jean; Boulbes, Nicolas; Boutié, Paul; Cretin, Catherine; Crégut-Bonnoure, Évelyne; Duzer, Danièle; Jolly, Dominique; Laudet, Frédéric; Lefévre, David; Mourer-Chauviré, Cécile; Rousselières, France; et al. (Comptes Rendus Palevol, 2007)
The Marie cave, discovered to the north of Montpellier, Herault (France), has yielded a fauna of 28 vertebrates, out of which 23 are small ´ to large mammals, notably Mammuthus primigenius. The few discovered artefacts have been attributed to the Upper Palaeolithic, which is in agreement with the two radiocarbon dates (31450 14 C yr BP for the low level, and 28680 14 C yr BP near the cave’s entrance). The palynological study shows the existence (i) of a wooded steppe on the plateau, and (ii) of a riverine forest with alders in the valleys, associated with Mediterranean taxa. These data conﬁrm the presence in Languedoc of Mediterranean species around 30000 yr BP, which qualiﬁes the hypothesis of exclusively Spanish and Italian refuges during glacial periods
Keywords: France; Marie cave; Palaeoenvironment; palynology; Upper Palaeolithic; Vertebrates; Wurm

Réponse des coléoptères saproxyliques à l’hétérogénéité des subéraies dans le massif des maures (France) - Brin, A. ; Brustel H. (Revue d'Ecologie la Terre et la Vie, 2006)
Saproxylic beetles’ response to cork-oak forests heterogeneity in the Massif des Maures (France). — Cork-oak stands are a major component of the “Massif des Maures” forests (France, Var). Depending on fi re frequency, soil conditions and human uses, these forests present different forms. Even if Mediterranean landscapes have been shaped for a long time by fi re, such recurrent perturbation may affect several functional groups of organisms associated with old forests, such as saproxylics insects. Our aims were (i) to investigate species richness and composition of saproxylic beetle assemblages in different cork-oak stands, (ii) to estimate between stand complementarity and (iii) identify indicator species of each habitat. Three different types of cork-oak stands common in the “Massif des Maures”, representing an increasing gradient of canopy closing and ecosystem maturing, were investigated : a senescent stand associated with mature maquis, an adult stand with high maquis and an open adult stand with low maquis. Beetles were sampled from April to August in 2003 and 2004 using baited window traps. Our results showed that : (i) the three studied cork-oak stands can be considered as three different habitats regarding saproxylic beetle assemblages, (ii) the closed cork-oak stands support the highest cumulative species richness, (iii) abundances of ecological groups show signifi cant between stands differences, (iv) each habitat supports remarkable species from a patrimonial point of view.
APSAPS
Keywords: Cork oak; France; saproxylic beetles

Congruency analysis of species ranking based on leaf traits: which traits are the more reliable? - Roche, Philip; Díaz-Burlinson, Natalia; Gachet, Sophie (Plant Ecology formerly `Vegetatio', 2004)
Nine leaf traits area, fresh weight, dry weight, volume, density, thickness, speciﬁc leaf area SLA, dry matter content LDMC, leaf nitrogen content LNC from ten plant species at eight sites in southern mediterranean France were investigated in order to assess their variability along a climatic gradient and their ranking congruency power. After examination of trait correlation patterns, we reduced the nine initial leaf traits to four traits, representative of three correlation groups: allometric traits dry weight, functional traits SLA and dry matter percentage and Leaf Thickness. We analysed the variability of these four leaf traits at species and site level. We observed that between species variation between 64.5 for SLA and 91% for LDMC is higher than within species variation. Allowing a good congruency of species ranking assessed by spearman rank correlation and a good reallocation of individuals to species by discriminant analysis. A site level variability between 0.7% for Dry weight and 6.9% for SLA was identiﬁed and environmental parameters altitude, temperature, precipitation, nitrogen, pH were considered as probable control factors. We found signiﬁcant correlation between SLA, LDMC and the average minimum temperature respectively r0.87 and r-0,9 and no correlation for the other traits or environmental parameters. Furthermore, we conclude that two leaf traits appear to be central in describing species: speciﬁc leaf area SLA, percentage of dry matter LDMC. While, SLA and LDMC are strongly correlated, LDMC appears to be less variable than SLA. According to our results the Dry Matter Content or its reversal Leaf Water Content appears the best leaf trait to be quantiﬁed for plant functional screening. Leaf thickness appeared to be rather uncorrelated with other leaf traits and show no environmental contingency; its variability could not have been explained in this study. Further studies should focus on this trait.
Keywords: dry matter content; France; Mediterranean; sla

BIRD-DISPERSED SEED RAIN AND SEEDLING ESTABLISHMENT IN PATCHY MEDITERRANEAN VEGETATION - Debussche, M.; Isenmann, P. (OIKOS, 1994)
The composition and spatial patterns of the seed rain produced by bird dispersers and of the seedlings of fleshy-fruited plants have been studied in patchy Mediterranean vegetation in southern France. The seeds of fleshy-fruited plants were collected in seed traps during a 17-month period (1981-1983) and the fecal samples of bird dispersers mist-netted on the same 2.5-ha site over a 25-month period (1981-1984) were analysed. The locations of the 5 sets of seed traps and the 6 mist-nets were chosen in order to take into account the various plant communities and the successional gradient from old fields to Quercus ilex coppice. Seedling establishment of fleshy-fruited plants was censused in 1983 adjacent to the seed traps. In 1992 seedlings were again censused in the open coppice and in the old fields. The seeds of 38 fleshy-fruited plants were collected, including 13 alien and cultivated species. Among them, 25 species were dispersed by Sylvia atricapilla, which dispersed the most diverse and mixed seed rain of the various bird dispersers. Species richness of the seed rain increased log-linearly with seed density, ranging from 3 to 21 species per 0.25 m2. Seed density was very heterogeneous in space. The maximum density of seeds was observed under the canopy of isolated trees and saplings in the old fields (up to 829 per 0.25 m2) which are the favoured perching places for the dispersers. Minimum density was observed in the same old fields outside the canopy of these same trees and saplings (down to 12 per 0.25 m2). In the Quercus ilex coppice, the higher the canopy, the higher the seed density. Dispersal was a short distance process. A large majority of the seeds of Pyracantha coccinea and Sambucus nigra were dispersed by birds less than 100 m from the maternal plant. However, a dispersal distance of > 300 m was observed for a seed of Ligustrum vulgare, In 1983 the < 1 yr-old seedlings of 17 fleshy-fruited plants, including only one alien species, and the 1-2 yr-old seedlings of 7 native species were censused. Though important components of the seed rain, no 1-2 yr-old seedlings of several alien (e.g. Pyracantha coccinea) or native (e.g. Rhus coriaria) species were observed in the studied vegetation. Seedlings were more numerous under tree cover than in the coppice clearings. In the old fields, < 1 yr-old seedlings were more numerous under the canopy than in open areas. No such difference was observed under saplings in 1983 and very few seedlings were observed in the old fields. The 1992 census suggested that the positive role of the cover of pioneer plants on seedling establishment progressively increased with successional development. This is probably due to an increase in the nurse effect and a decrease in the herbaceous cover under the canopy. It is suggested that. in old fields. the establishment of fleshy-fruited plants is favoured when seeds are deposited under pioneer woody plants rather than in open areas. The bird dispersers thus trigger dynamic processes initiated by the pioneer woody plants in Mediterranean old field succession. More generally, dispersal of fleshy-fruited plants by birds is more significant in the central stages of succession gradient than it is in open herbaceous communities and in dense forest when both have an homogeneous structure.
APSAPSThe following values have no corresponding Zotero field: pub-location: 35 NORRE SOGADE, PO BOX 2148, DK-1016 COPENHAGEN, DENMARK publisher: MUNKSGAARD INT PUBL LTD
Keywords: bird dispersers; fleshy-fruited; France; Mediterranean; Quercus ilex; seedlings

THE IMPORTANCE OF TERRITORIAL BEHAVIOR AMONG BLUE TITS (PARUS-CAERULEUS) BREEDING IN A HOLM OAK FOREST - Clamens, A. (Revue D Ecologie-La Terre Et La Vie, 1987)
In a ringed population of Blue Tits (Parus caeruleus) living in a Holm Oak (Quercus ilex) forest of Languedoc, Southern France, and provided with artificial nest-boxes, territorial behaviour plays a major role in limiting the number of breeding pairs. The experimental removal, or the spontaneous disappearance, of a breeding pair is followed by an increase in size of the territories of the neigbouring pairs, or by the arrival of non-ringed juvenile individuals settling in the vacant territory. In a Holm Oak forest without artificial nest-boxes, territorial behaviour does not play such a role, as the major limiting factor in that case is the number of available tree-holes. Pairs of Blue Tits settled on territories where Downy Oaks (Quercus pubescens) are mixed with Holm Oaks, lay their eggs four days earlier on the average, than Blue Tits breeding in pure Holm Oak forest. However, the number of fledglings per brood, and their body weight at 15 days of age, tend to be smaller. The benefit of a later laying date in pure Holm Oak forest quite likely lies in a better synchronization of the maximum nutritional requirements of the young, and of the period of maximum food availability in the environment.
APSAPSThe following values have no corresponding Zotero field: label: Biodiversidade
Keywords: Biodiversidade; breeding pairs; France; holm oak forests; nest-boxes; Parus caeruleus; Quercus ilex